New Method of Tooth Pitch Deviation Measurement based on Laser Tracker for Mega Spur Gear - Zhang Bai; Lin Jiachun (Jixie chuandong)
To measure pitch deviation of mega spur gears, a new method for measuring the pitch of mega spur gears based on laser tracker is proposed. The measuring ability of laser tracker in large space is used to measure gear groove, and two adjacent pitch error curves of measured mega spur gear are obtained respectively. Because of the diameter of measured gear exceeds 6 meters, the single pitch error can be approximately calculated according to the formula of point-to-line distance. Firstly, the pitch measurement model of the gear workpiece coordinate system based on laser tracker is analyzed, and according to the characteristics of the mega spur gear, the pitch error measurement model of the mega spur gear without coordinate system based on laser tracker is proposed. The measurement model avoids the establishment of workpiece coordinate system of mega gear and directly measures tooth space with two-sided contact condition. By evaluating the errors of two measuring straight lines of the tooth space, the max single pitch error and the average single pitch deviation can be obtained. By transferring station measurement of laser tracker, total cumulative pitch deviation can be obtained. Finally, the uncertainties of system measurement of different measurement model are simulated and analyzed by the Monte Carlo method. The experimental results show that the method for measuring the pitch of mega spur gears based on laser tracker meets the single pitch deviation measurement requirements of 8-grade mega spur gears with diameter of more than 6 meters, and meets the total cumulative pitch deviation measurement requirements of 10-grade mega gears with diameter of more than 6 meters.